Computational design and validation of siRNA molecules to silence oncogenic CTNNB1 mRNA as a potential therapeutic strategy against hepatitis B/C virus-associated hepatocellular carcinoma - Lauren Emily Fajardo; Mark Andrian Macalalad; Nyzar Mabeth Odchimar; John Christian de Guzman; Fredmoore Orosco (Pensoft Publishers, 2024)
The majority of hepatocellular carcinoma cases are caused by infection with hepatitis B (HBV) or C (HCV) viruses. CTNNB1 is the most mutated oncogene in HBV- and HCV-associated tumors. CTNNB1 mutations can lead to β-catenin accumulation, resulting in tumor progression. Small interfering RNAs (siRNAs) can be used to silence CTNNB1 mRNA. After prediction and evaluation, four siRNAs were found to have the highest silencing potential. All four siRNAs had an acceptable GC content, no palindromic sequences, no off-targets, were thermostable, and had accessible target sites. Molecular docking of the siRNAs to Argonaute 2 demonstrated favorable docking scores within the binding pocket for three siRNAs. Molecular dynamics simulations and binding energy calculations demonstrated that the siRNAs steadily remained in the binding pocket. In this study, three siRNAs were successfully designed to silence oncogenic CTNNB1 mRNA as a therapeutic strategy against hepatocellular carcinoma and warrant further in vitro and in vivo validation.